Determinants of economic growth in BRIC countries - Rajjev K. Goel; Iikka Korhonen (Institute for Advanced Development Studies (INESAD), 2011)
We study economic growth in four emerging economies - Brazil, Russia, India, and China (BRIC). Questions addressed are: (a) How do medium term growth determinants differ from short term determinants? (b) What are differences between growth effects of aggregate versus disaggregated exports? And (c) Does lower institutional quality hinder growth? Results show that while BRIC nations have higher growth, there are significant within-group differences. China and Russia mostly showed higher growth, while India sometimes showed positive growth, and Brazil did not outperform the rest. Policy implications are discussed.
Keywords: O40; O57; P52; 330; Economic growth; BRIC countries; Exports; Institutions; Corruption; World; Wirtschaftswachstum; Export; BRICS-Staaten